Studi Literatur: Faktor Risiko dan Strategi Pengendalian Fasciolosis di Indonesia - Charisma, Acivrida Mega; Ekawasti, Fitrine; Wahyuningrum, Arina; Naisali, Walburga F. F.; Syawaludin, Moch. Fardha; Auralya, Theresia Feby; Vebiayanti, Saski Dwi; Maisaroh, Maisaroh; Rukmana, Dinda Herdiana; Alfani, Moh.; Afkarina, Zida Kamalia (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2024)
Fasciola hepatica is the main species found infecting livestock. Fasciolosis is a significant animal health and public health problem, causing major economic losses. Epidemiological studies of fasciolosis in dairy cattle in Indonesia are still few and existing reports only focus on prevalence. Fasciolosis is an endemic parasitic disease in Indonesia and causes considerable economic losses. Efforts that can be made to prevent disease are vector eradication, namely eradicating snails through biological means, for example by raising ducks. Raising ducks biologically can reduce the worm population. Several simple techniques for controlling worm infections in cattle can be done by regulating feeding, timing grass cutting and making compost to break the life cycle of Fasciola sp. In general, dairy cattle in Indonesia are raised more intensively compared to beef cattle farms, which explains the difference in prevalence rates. In intensive farming systems, animals are housed permanently, limiting their exposure to parasite-contaminated grass compared to pastured animals.